(untitled) (Global Journal of Science Frontier Research, 2016)
We investigate the effects of the wind shears and nonisothermality on the ray propagation of acoustic-gravity waves in a nonhydrostatic atmosphere by generalizing Marks & Eckermann’s WKB ray-tracing formalism (1995: J. Atmo. Sci., 52, 11, 1959Sci., 52, 11, -1984;; cited as ME95). Five atmospheric conditions are considered, starting from the simplest isothermal and shearfree case. In every step case a set of ray equations is derived to numerically code into a global raytracing model and calculate the profiles of ray paths in space and time, wavelengths and intrinsic wave periods along the rays, meanfield temperature or horizontal zonal/meridional wind speeds, as well as their gradients, and the WKB criterion parameter, . Results include, but not limited to, the following: (1) Rays in shear-free and isothermal atmosphere follow straight lines in space; both forward and backward-mapping rays are superimposed upon each other; wavelengths ( x,y,z ), as well as the intrinsic wave period ( ), keep constant versus altitude. (2) If Hines’ locally isothermal condition is applied, i.e., including the effect of temperature variations in altitude, ray traces become non-straight; however, their projections in the horizontal plane keep straight; the forward and backward ray traces are no longer overlain; and, show discernable changes but does not change. All the modulations happen at around 80-150 km altitudes.